AB1086 Evaluation of the Properties of the Rheumatoid Arthritis Impact of Disease (RAID) Score in Multiethnic Asian Patients with Rheumatoid Arthritis. (10th June 2014) - Cheung, P.; Lahiri, M.; Teng, G.G.; March, L.; Gossec, L.
Abstract : Background: The RAID is a patient reported outcome (PRO) measure evaluating the impact of rheumatoid arthritis (RA) on patients' quality of life. It comprises 7 domains (pain, function, fatigue, physical and psychological wellbeing sleep disturbance and coping), that are evaluated as continuous variables from 0 (best) to 10 (worst) [1], validated predominantly in Caucasians. The final score ranges from 0-10. It has not been applied in Asian populations, who may have different reporting of PROs and life impact. Objectives: To evaluate the metrological properties of RAID in a multiethnic Asian RA cohort, and to compare these properties to those reported in the initial study of the RAID in a predominantly Caucasian population. Methods: Cross-sectional assessment of consecutive RA patients in a Singapore tertiary centre was performed. Validity was assessed by measuring correlation with patient global assessment (PGA), disease activity score in 28 joints (DAS28) and short form 12 (SF-12) (Spearman's). Consistency and reliability were assessed by Cronbach's alpha and by intra-class correlation coefficient (ICC) respectively. The cut-off for patient acceptable state was evaluated by receiver operator curve (ROC) analysis. To determine the variance in RAID attributable to different factors (calculation of R 2 ), two separate multiple linear regressions were performed, one with patient-related explanatory variables (i.e., ethnicity, education, sex, body mass index or BMI, age, smoking) and the other with disease-related variables (i.e., DAS28, the 8-question modified-Health Assessment Questionnaire, mHAQ, SF-12, PGA, presence of either rheumatoid factor or anti-CCP). Results: In all 101 RA patients (76% Chinese, 12% Malay, 12% Indian) were analysed: mean age 54.5±12.8 yrs, disease duration 6.3±6.0 yrs, and 80% women. Mean RAID score was 2.5±2.0, DAS28 was 3.3±1.1 and mHAQ was 0.1±0.3. RAID was strongly correlated with PGA (R=0.75), and weakly but significantly correlated with other outcomes (DAS28 R=0.44, SF12 physical −0.40 and mental −0.50, p<0.0001 for all). Consistency and reliability was high with Cronbach's alpha=0.91 and ICC=0.84 (95% CI: 0.74–0.90) respectively. The cut-off point for a patient acceptable symptom state was below 2.24. By linear regression, demographic variables explained 2.2% of the variance of the RAID whereas disease characteristics and activity explained 65.9% of the variance of the RAID. Conclusions: The RAID may be a valid and practical PRO to assess the impact of RA in Asia. The metrological properties of RAID in this multiethnic Asian cohort are comparable to that of the original RAID-development Caucasian RA population, although sensitivity to change needs to be further evaluated. References: Gossec et al. Ann Rheum Dis 2009;68:1680-5. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1794